Challenges in Reducing Readmissions: Lessons from Leadership and Frontline Personnel at Eight Minority-Serving Hospitals - Joynt, Karen E. (Jt Comm J Qual Patient Saf, 2014)
BACKGROUND: Hospitals that serve minority patients have higher readmission rates than other hospitals and, as a result, receive higher penalties under the federal government’s Hospital Readmissions Reduction Program. A study was conducted to determine how minority-serving hospitals are responding to federal readmissions policy and whether they face specific challenges as they work to reduce readmissions. METHODS: In-depth case studies were created for eight minority-serving hospitals, selected to reflect a range of geographies and sizes. Semistructured interviews with hospital leaders and frontline personnel focused on knowledge of readmission rates and prioritization of readmission reduction, strategies to reduce readmissions, barriers to reducing Readmissions, and opinions about federal readmissions policy. RESULTS: Each hospital had only a general awareness of its performance on readmissions metrics but placed a high priority on reducing readmissions, largely spurred by federal readmissions policy. Respondents reported that socioeconomics, rather than race alone, was a key factor in readmissions reduction. The hospitals followed a similar progression in strategies to reduce readmissions—moving from working on the discharge process to creating customized approaches to transitional care to, finally, focusing more on building community supports and resources. Salient barriers to reducing readmission rates included scarce resources, the variety of patient needs, limited ability to influence care in the community, and a misalignment of financial incentives. CONCLUSIONS: Among eight hospitals serving a high proportion of minority patients, the findings uncovered the importance of addressing issues specific to the patient population and community and reaching outside the walls of the hospital to implement programs that improve outpatient access and management.